Highly Sensitive Capsaicin Electrochemical Sensor Based on Bimetallic Metal-Organic Framework Nanocage - Fang, Xiao; Duan, Rongshuai (Frontiers in Chemistry, 2022)
The content of capsaicin can be used as exotic markers of kitchen recycled oil. In this study, a bimetallic MOF nanocage (FeIII-HMOF-5) was successfully prepared by a one-step solvothermal method and used for electrode modification to prepare a highly sensitive electrochemical sensor for rapid detection of capsaicin. Capsaicin could be selectively immobilized onto the FeIII-HMOF-5 surface during infiltrating adsorption, thus exhibiting very excellent sensing performance. The detection conditions of the sensor were optimized. Under optimum conditions, the electrochemical sensor can linearly detect capsaicin in the range between 1–60 μM with a detection limit of 0.4 μM. In addition, the proposed electrochemical sensor showed excellent stability and selectivity. The real sample tests indicated the proposed electrochemical sensor was comparable to conventional UV spectrophotometry.